PERSEPSI MAHASISWA TERHADAP GURU BIMBINGAN KONSELING DALAM MENGARAHKAN SISWA KE JENJANG SELANJUTNYA - Siti Mutiara Sari; Gina Alzena (BIMBINGAN DAN KONSELING BANYUWANGI, 2025)
This study aims to determine how far the role of counseling guidance in directing students for career determination to the next level through the perceptions of 26 students of Architectural Engineering Education, University of Education Indonesia, this type of research is descriptive quantitative. The data collection technique uses a questionnaire with google form media while data analysis uses descriptive percentages. The results showed that 20.2% of respondents had a very good perception of the role of counseling guidance teachers in directing students to the next level. then, 20.8% of respondents did not feel the role of counseling guidance teachers in directing students to the next level. The average perception of respondents regarding the role of counseling teachers is quite good with a percentage of 58.7%. It can be concluded that the higher the role of counseling guidance teachers in providing direction, the higher the perception of students. Conversely, if the role of the counseling guidance teacher is less, the perception will also be less.